(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
During the simultaneous electro-spark dispersion of silver and tin in water, nanoparticles of the solid solution Ag₃Sn, metallic β-Sn, as well as tin oxides are formed. The obtained nanocomposites were studied for biological activity using wheat seeds of the “Zhiger” variety. It was found that Ag–Sn nanocomposites synthesized in an aqueous medium significantly increase seed germination and stimulate plant growth. Compared to the control, the length and thickness of seedling roots increased markedly. After two weeks, the root length of treated seeds reached 11–13 cm, whereas in the control variant shorter and weaker roots were formed. The obtained results indicate high biological activity of the Ag–Sn nanocomposite system.